Occurrences of Dengue Fever, Dengue Hemorrhagic Fever, Dengue Shock Syndrome, Severe Dengue, Dengue Warning Signs in Bandung City: An Spatial Study Based on Moran Index - Firmansyah, Yura Witsqa; Parulian, Adi Anggoro; Kristiawan, Hedie; Prasaja, Bhisma Jaya (Lontara Journal of Health Science and Technology, 2024)
Dengue cases is a tropical disease transmitted by Aedes aegypti and Aedes albopictus mosquitoes, which has become an international health issue in recent decades. The purpose of this study is to determine the autocorrelation and distribution patterns of Dengue Fever (DF), Dengue Hemorrhagic Fever (DHF), Dengue Shock Syndrome (DSS), Severe Dengue (SD), and Dengue Warning Signs (DWS) in the operational area of Hospital X. This study is classified as correlational, with a retrospective cohort design, utilizing patient medical records from January 2 to May 15, 2024. The total sample consists of 1,698 records, collected through purposive sampling, with the criteria being patient medical records diagnosed with DF, DHF, DSS, SD, and DWS during 2024. The z-score indicates that clustered distribution patterns occur in DF cases (z-score 5.07) and DHF cases (z-score 9.85). Random distribution patterns occur in DSS cases (z-score 0.86), SD cases (z-score -0.35), and DWS cases (z-score -0.15). The hypothesis that shows autocorrelation (p-value 0.000) is that the occurrence of DF in one location correlates with DF occurrences in surrounding locations, and the occurrence of DHF in one location correlates (p-value 0.000) with DHF occurrences in surrounding locations